CIPP Evaluation of Literature Learning in the Indonesian Language Education Study Program - Armariena, Dian Nuzulia; Nuryatin, Agus; Supriyanto, Teguh; Setyaningsih, Nas Haryati (Universitas Negeri Semarang, 2025)
The goal of learning literature is to enhance students' language skills and broaden their understanding of literary texts. This includes improving reading comprehension, expanding vocabulary, and developing speaking and writing abilities, which are essential for effective language communication. This study is based on creating a literary learning model that promotes student creativity and self-evaluation as a more engaging way to appreciate literature. With the CIPP evaluation method that emphasizes the process and product components, it is necessary to evaluate literature education by creating a learning model that relates to a comprehensive understanding of learning plans and their effectiveness. The research was conducted at Unsri, Unanti, and UPGRIP. Data for this study was gathered using document review techniques, which were then analyzed using descriptive analysis methods. The study discovered that the method of teaching appreciative literature varies. The items are also varied. The goal of the curriculum—that students learn to appreciate, express, and produce literature—has, however, been mostly accomplished by literary appreciation education. The context variables in this scenario have a greater influence on the process than the produced input. The context here refers to the students' academic success, their good conduct, and their genuine interest in literature. Furthermore, the context also refers to experienced instructors and individuals who take the learning process seriously in order to accomplish their goals. The research indicates that the assessment of literature instruction in terms of both its process and outcomes falls under the